Canoe-carving, Lamotrek style : An interdisciplinary study in crafting, design, engineering, and sustainability - Penny, Simon (FormAkademisk, 2021)
Micronesian traditional canoe carvers of Lamotrek Atoll are one of the few Pacific communities whose canoe carving, ocean seafaring and indigenous navigation techniques are living traditions. They sail long distances on open ocean in these craft without instruments or maps, using traditional navigation techniques. Their building procedures involve no plans, no measuring devices or numbers. This kind of indigenous boatbuilding and seafaring was once practiced by virtually all Pacific island communities over hundreds or thousands of years, but the traditional knowledge has been eradicated in all but the most isolated and impoverished communities.